2018
DOI: 10.2147/jbm.s157633
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypical variability in congenital FVII deficiency follows the ISTH-SSC severity classification guidelines: a review with illustrative examples from the clinic

Abstract: BackgroundOne of the most common rare inherited bleeding disorders, congenital factor VII (FVII) deficiency typically has a milder bleeding phenotype than other rare bleeding disorders. Categorizing severity in terms of factor activity associated with hemophilia (severe <1%, moderate 1%–5%, mild 6%–40%) has led to the observation that bleeding phenotype does not follow closely with FVII activity. Over the past decade, large-scale global registries have investigated bleeding phenotype more thoroughly. The Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…1 We decided to adhere to the classification proposed by Jain et al with FVII:C below 1% corresponding to severe and 1 to 5% to moderate deficiency. 12 The additional cut-off set at 15% reflects, as clarified before, the suggested minimal level protecting from spontaneous bleeds. 3,5,10 The true haemostatic threshold of FVII activity is not known.…”
Section: Discussionmentioning
confidence: 99%
“…1 We decided to adhere to the classification proposed by Jain et al with FVII:C below 1% corresponding to severe and 1 to 5% to moderate deficiency. 12 The additional cut-off set at 15% reflects, as clarified before, the suggested minimal level protecting from spontaneous bleeds. 3,5,10 The true haemostatic threshold of FVII activity is not known.…”
Section: Discussionmentioning
confidence: 99%
“…After further analysis of the reported cases, the most common conclusion is that the FVII activity level, FVII genotype, coagulation test, and bleeding history could not predict the bleeding risk of patients with FVIID[ 14 ]. In preliminary studies, some patients with FVII activity lower than 8% showed mild symptoms or no symptoms; 12 patients with no previous bleeding history and 44% FVII activity had delayed intracranial hemorrhage[ 5 ]. In this case, the activity of FVII fluctuated between 2.00%-6.30% and PT fluctuated between 38.2-62.10 s when the drug was not used.…”
Section: Discussionmentioning
confidence: 99%
“…The International Society of Thrombosis and Hemostasis classifies FVIID as follows: severe: FVII < 10%, with the risk of spontaneous bleeding; moderate: FVII 10%-20%, with the risk of mild spontaneous or trigger bleeding; mild: FVII 20%-50%, most of them are asymptomatic[ 5 ]. The Seven Treatment Evaluation Registry defined FVII activity among severe patients as ≤ 5%[ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Эти факты дают основание усомниться в клинической значимости существующих классификаций гипопроконвертинемии в зависимости от плазменной активности FVII. Наиболее распространена классификация, предложенная Международной ассоциацией по тромбозу и гемостазу (The International Society on Thrombosis and Haemostasis, ISTH), согласно которой тяжелая форма характеризуется снижением активности FVII менее 10% и высоким риском больших спонтанных кровотечений и кровоизлияний; средней тяжестиактивностью фактора 10-20% с риском небольших спонтанных или спровоцированных кровотечений, легкая форма -активностью фактора 20-50% с отсутствием клинических проявлений [8].…”
Section: описание случаевunclassified